The happy prince and The nightingale and the rose - Wilde, Oscar (Helbling Readers. Red Series)
The Happy Prince is the story of a piccola rondine that interrupts his journey to the sole to help a prince with a big heart to make his popolo happy. L'usignolo, protagonista di The Nightingale and the Rose, si dimostrerà più esperto d'amore del giovane personaggio della storia. Helbling Readers Red Series is a series of graduate letters to illustrate, create and think purposefully for the ragazzi. Le letter sono graduate in 3 livesli corresponding to those of the Quadro Comune Europeo di Referimento. This text is part of the Helbling Classics, a series of classics written by the most authoritative English literature, carefully selected according to the level of content that follows the linguistic level. Added by Maria Cleary. Registration in British English.